2020
DOI: 10.1097/md.0000000000022594
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of blood-based liquid biopsies in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is an aggressive cancer associated with poor prognosis. Early diagnosis is crucial to improve its prognosis. Blood-based liquid biopsies are promising methods in detecting HCC. However, their accuracies have not been systematically assessed, so it is essential to conduct a meta-analysis to evaluate the diagnostic performance of blood-based liquid biopsies in detecting HCC. Methods: We will search PubMed, EMBASE, Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Additionally, osteoarthritis is a common disease of progressive destruction of articular cartilage, accompanied by increased pain, currently lacking effective drugs targeting cartilage repair and regeneration (Li et al, 2013). MSC-Exos are effective at promoting bone repair and regeneration independently, and play an immunomodulatory role by binding with receptors to promote osteogenesis (Zhang et al, 2020b;Fan et al, 2021). Current research suggests that MSC-Exos can promote osteogenic differentiation and angiogenesis, regulate immune function, induce chondrogenesis and improve osteoporosis (Lu et al, 2019;Yang et al, 2021).…”
Section: Relationship Between Msc-exos and Bone Repair And Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, osteoarthritis is a common disease of progressive destruction of articular cartilage, accompanied by increased pain, currently lacking effective drugs targeting cartilage repair and regeneration (Li et al, 2013). MSC-Exos are effective at promoting bone repair and regeneration independently, and play an immunomodulatory role by binding with receptors to promote osteogenesis (Zhang et al, 2020b;Fan et al, 2021). Current research suggests that MSC-Exos can promote osteogenic differentiation and angiogenesis, regulate immune function, induce chondrogenesis and improve osteoporosis (Lu et al, 2019;Yang et al, 2021).…”
Section: Relationship Between Msc-exos and Bone Repair And Regenerationmentioning
confidence: 99%
“…Macrophages as immune cells play a crucial role in bone regeneration, secreting inflammatory and chemotactic mediators, and initiating the recruitment of MSCs (Loi et al, 2016). MSC-Exos possess a sustained inflammation-regulatory ability, which could decrease the gene expression of IL-1β, IL-6, TNF-α, and suppress the expression of an M1 phenotypic marker (iNOS) mRNA in the inflammatory macrophages (Wei et al, 2019;Zhang et al, 2020b). The scanning electronic microscopy results depicted that the morphology of macrophages was significantly elongated after treatment with BMSC-Exos.…”
Section: Immunoregulationmentioning
confidence: 99%
“…If I 2 > 50%, the heterogeneity across studies was significant, and a random-effects model was used in the meta-analysis; otherwise, a fixed-effects model was used. [ 23 ] Numerical values for pooled sensitivity, pooled specificity, positive likelihood ratio (LR), negative LR, and diagnostic odds ratio (DOR) were obtained from FN, FP, TN, and TP. These were presented alongside graphical representations, wherein the horizontal lines showed the confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was indicated by I 2 , where 0% means no heterogeneity and 100% means the strongest heterogeneity. If I 2 > 50%, the heterogeneity across studies was significant, and a random-effects model was used in the meta-analysis; otherwise, a fixed-effects model was used [23] . Numerical values for pooled sensitivity, pooled specificity, positive likelihood ratio (LR), negative LR, and diagnostic odds ratio (DOR) were obtained from FN, FP, TN, and TP.…”
Section: Methodsmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses showed that genomic profiling of liquid biopsy is a promising strategy in the identification of individual mutational patterns of HCC patients. However, the examination of liquid biopsy has relatively low sensitivity and high specificity in the early detection of HCC and there is a risk of bias (24)(25)(26). Therefore, accurate phenotyping and genotyping of liquid biopsy are of crucial importance.…”
mentioning
confidence: 99%